Entrepreneurial index for low-income households in Malaysia. (October 2021) - Al Mamun, Abdullah; Thurasamy, Ramayah; Fazal, Syed Ali
Abstract: Even though development organizations provide access to working capital and enterprise development training, they often fail to improve the socio-economic condition of low-income households. One of the factors contributing to the failure of development programs is their lack of capacity to measure the entrepreneurial potentials among the low-income participants. This study focused on the development of an entrepreneurial index that measures the entrepreneurial potentials among low-income households. Adopting a cross-sectional design, a total of 403 micro-entrepreneurs were approached from the list provided by ' Majlis Amanah Rakyat' and ' Majlis Agama Islam Dan Adat Istiadat ', Kelantan. This study used formative hierarchial model to determine the local and global weights for all the items used to develop the index. Further, the nomological validity revealed a positive effect of entrepreneurial index on entrepreneurial competency, enterprise performance, and enterprise sustainability. Highlights: Focused on the development of an entrepreneurial index that measures the entrepreneurial potentials. Used formative hierarchical model to develop the index for low-income participants. Conducted focus group discussion and collected quantitative data from micro-entrepreneurs. Five dimensions includes entrepreneurial orientation, traits, motivation, leadership, and knowledge and skills. Findings confirmed the nomological validity of the entrepreneurial index.